PENATAAN SUMBER DAYA MANUSIA APARATUR DAERAH BERBASIS KOMPETENSI - Irma Purnamasari; R. Akhmad Munjin; Ike A Ratnamulyani (Jurnal Governansi, 2019)
The implementation of Regional Government is directed at accelerating the realization of community welfare through improving services, empowerment, and community participation. In an effort to achieve the above goals, apparatus with the right, professional and competent numbers are needed. In line with the principles of professionalism and objectivity that are required in the law on staffing matters, the Bureaucratic Reformation in the Regional Government needs to conduct competency-based Apparatus Resource Arrangements. Presidential Regulation Number 81 of 2010 concerning Grand Design of Bureaucratic Reform explains that the main problem of state apparatus HR is the allocation in terms of quantity, quality, and distribution of civil servants according to unequal territorial (regional), and low levels of civil servant productivity. Structuring the human resources of the apparatus has not been optimally implemented to improve professionalism, employee performance, and organization. The research method used is descriptive qualitative through (1) desk study (study of literature and documents) and (2) field study (field study) that uses observation and interview techniques. Competency-based Apparatus Resource Management implies the need for the availability of information relating to competence. In this case the two main pillars are the competencies required by the office, commonly referred to as Position Competency Standards and the competencies possessed by employees.Keywords: Apparatus HR Management, Employee Competence, Regional Apparatus HR.